Functioning of Neurotypical Siblings of Individuals with Autism Spectrum Disorder: A Systematic Review - Brenda Cervellione; Calogero Iacolino; Alessia Bottari; Chiara Vona; Martina Leuzzi; Giovambattista Presti (Psychiatry International)
Neurotypical (NT) siblings of individuals with Autism Spectrum Disorder (ASD) experience complex emotional, psychological, behavioral, and social challenges. Understanding the factors that influence their well-being is essential for developing tailored interventions. This systematic review examines the psychological and social functioning of NT siblings and identifies protective and risk factors that impact their adaptation. A systematic search was conducted across EBSCO, PubMed, and Google Scholar, covering studies published between 2013 and 2024. Inclusion criteria focused on research investigating NT siblings’ emotional, psychological, behavioral, and social well-being. Thirty studies met the inclusion criteria and were synthesized narratively. Findings reveal heterogeneous experiences among NT siblings, ranging from increased empathy and resilience to heightened anxiety, depression, and social difficulties. The quality of sibling relationships and social support systems plays a pivotal role in moderating these outcomes. NT siblings represent a vulnerable group requiring family-centered interventions. Future research should adopt longitudinal and multi-informant approaches to explore long-term effects and culturally sensitive support strategies.